2014
DOI: 10.1002/bip.22519
|View full text |Cite
|
Sign up to set email alerts
|

Solution structures and model membrane interactions of Ctriporin, an anti‐methicillin‐resistant Staphylococcus aureus Peptide from Scorpion Venom

Abstract: Ctriporin peptide (Ctr), a novel antimicrobial peptide isolated from the venom of the scorpion Chaerilus tricostatus, shows a broad-spectrum of antimicrobial activity and is able to inhibit antibiotic resistant pathogens, including Methicillin resistant Staphylococcus aureus, Methicillin Resistant Coagulase-negative Staphylococcus, and Penicillin Resistant Staphylococcus epidermidis strains. To understand the active conformation of the Ctr peptide in membranes, we have investigated the interaction of Ctr with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…The solution structure of carnocyclin A was obtained using water as the solvent, while for acidocin B, a membrane-mimicking SDS micelle was employed. Studies have shown that certain peptides undergo conformational changes from a free state in water to a membranebound form in membrane mimetic solvents (52,53,54). The structure of carnocyclin A in water shows that helix 3 is almost perpendicular to helix 1 (17), while helix 1 and 3 of acidocin B are almost parallel.…”
Section: Discussionmentioning
confidence: 99%
“…The solution structure of carnocyclin A was obtained using water as the solvent, while for acidocin B, a membrane-mimicking SDS micelle was employed. Studies have shown that certain peptides undergo conformational changes from a free state in water to a membranebound form in membrane mimetic solvents (52,53,54). The structure of carnocyclin A in water shows that helix 3 is almost perpendicular to helix 1 (17), while helix 1 and 3 of acidocin B are almost parallel.…”
Section: Discussionmentioning
confidence: 99%
“…But solid-state NMR is an approach used to analyze their interaction with membrane mimetics, such as vesicles containing different phospholipids, with phosphatidylcholine or phosphatidylglycerol being the most used. By altering the proportion of these lipids and using solid NMR analysis, it is possible to assess their interaction with different vesicle compositions, and thus, the specificity of these peptides ( Bandyopadhyay et al, 2014 ; Nomura et al, 2014 ).…”
Section: Structural Analysis Through Nuclear Magnetic Resonancementioning
confidence: 99%
“…It is possible to note from this table that AMPs from scorpions are mostly studied and analyzed using liquid-state NMR spectrometer functioning at 500–800 MHz, in water or TFE solution or in SDS or DPC micelles. When analyzing the same peptide in different solvents, it is possible to notice changes in the percentage of structure obtained; for example, ctriporin showed 73.6% of α-helix in SDS and 52.6% of α-helix in DPC micelles ( Bandyopadhyay et al, 2014 ). Therefore, it is important to assess the structure of these peptides in an environment that better mimics membranes to acquire the more accurate structure they show when acting on microbial membranes.…”
Section: Structural Analysis Through Nuclear Magnetic Resonancementioning
confidence: 99%